Performance characteristics in BMX racing: A scoping review - Rylands, L. P.; Roberts, S. (Journal of Science and Cycling, 2019)
Performance characteristics across a number of cycle sports have been investigated for decades. However, evidence suggests little is known about the performance characteristics in BMX cycling. As a result, a scoping review was undertaken to explore the quantity and themes of research in this area.